Case Study: Nursing Care for a Patient with Coronary Artery Disease (CAD) Using Benson Relaxation Technique to Reduce Pain - Wardana, Affan Hanafi; Kurniawan, Rudi; Nurapandi, Adi; Suhanda, Suhanda; Noviati, Elis (LPPM STIKes Muhammadiyah Ciamis, 2025)
Coronary artery disease (CAD) is a condition characterized by the narrowing or blockage of the coronary arteries, which are responsible for supplying oxygen-rich blood to the heart muscle. This condition is primarily caused by the accumulation of atherosclerotic plaque, including cholesterol and other substances, which progressively limits blood flow to the myocardium and may result in chest pain (angina) or even myocardial infarction. The purpose of this study is to explore the application of the Benson relaxation technique as a complementary intervention to reduce pain in patients diagnosed with CAD. This study employs a descriptive case study design, focusing on the nursing care of one patient using the nursing process approach to guide the intervention. The results of the case study indicate that prior to the implementation of Benson relaxation on June 24, 2024, the patient's reported pain level was at a scale of 4. After three consecutive days of applying the Benson relaxation technique, the pain scale decreased to 2. This demonstrates a reduction in perceived pain. However, the findings suggest that while Benson relaxation may contribute to pain reduction, its effectiveness as a standalone intervention is limited. Therefore, it is recommended that Benson relaxation be used as an adjunct to pharmacological therapy in managing pain among CAD patients.